2006
DOI: 10.1152/ajpheart.01146.2005
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal diastolic currents in ventricular myocytes from spontaneous hypertensive heart failure rats

Abstract: Abnormal diastolic currents in ventricular myocytes from spontaneous hypertensive heart failure rats. Am J Physiol Heart Circ Physiol 291: H2192-H2198, 2006. First published June 9, 2006 doi:10.1152/ajpheart.01146.2005.-Hypertension is a common cause of heart failure, and ventricular arrhythmias are a major cause of death in heart failure. The spontaneous hypertension heart failure (SHHF) rat model was used to study altered ventricular electrophysiology in hypertension and heart failure. We hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 43 publications
(49 reference statements)
1
23
0
Order By: Relevance
“…Strikingly, substantial up-regulation of I f expression has been observed in a variety of animal models of cardiac hypertrophy and heart failure and in human failing hearts as well (1-3, 9 -16). In such circumstances, I f is at least doubled in left ventricular (LV) 3 cells, depending upon severity of conditions (3,11,14), and reaches values comparable with those observed in the neonatal stage. Consistently, prominent re-expression of the I f -encoding genes, belonging to the hyperpolarization-activated cyclic nucleotide-gated channel (HCN) gene family in ventricular myocytes of hypertrophic heart has also been documented (17)(18)(19).…”
mentioning
confidence: 91%
“…Strikingly, substantial up-regulation of I f expression has been observed in a variety of animal models of cardiac hypertrophy and heart failure and in human failing hearts as well (1-3, 9 -16). In such circumstances, I f is at least doubled in left ventricular (LV) 3 cells, depending upon severity of conditions (3,11,14), and reaches values comparable with those observed in the neonatal stage. Consistently, prominent re-expression of the I f -encoding genes, belonging to the hyperpolarization-activated cyclic nucleotide-gated channel (HCN) gene family in ventricular myocytes of hypertrophic heart has also been documented (17)(18)(19).…”
mentioning
confidence: 91%
“…Abnormally enhanced automaticity of ventricular cells may contribute to arrhythmias in hypertrophied hearts. Consistent with this notion, robust enhancement of functional I f and upregulation of HCN gene expression have been observed in a variety of animal models of cardiac hypertrophy and heart failure and in human failing hearts as well [1,[6][7][8][9][10][11][12][13][14]. Normally, I f expresses in ventricular myocytes only during fetal and neonatal life and the abundance progressively decreases toward adulthood in terms of the number of cells expressing I f and of the density of expressed I f as well [4-6, 9, 12, 15, 16].…”
Section: Introductionmentioning
confidence: 53%
“…One of the characteristic alterations of hypertrophic hearts is the re-expression or overexpression of pacemaker channel genes thereby I f current, which may contribute significantly to the enhanced abnormality and the risk of arrhythmias under such pathological conditions [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. However, the mechanisms remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was observed that the upregulation of I f in diseased myocytes results in the occurrence of a diastolic depolarization in ventricular cells [6,42]. Experiments with adenoviral HCN2 constructs support these finding.…”
Section: Hcn4 Channelsmentioning
confidence: 84%